Effect of prepreg gaps and overlaps on mechanical properties of fibre metal laminates. (November 2018) - Abouhamzeh, M.; Nardi, D.; Leonard, R.; Sinke, J.
Abstract: During the automated manufacturing of fibre reinforced laminates, defects can be produced. Gaps and overlaps between adjacent prepreg layers can be produced in composites during the tape-layup process. However, the topic is not yet studied for hybrid materials, in which metal sheets and thin prepreg layers lead to different effects due to the defects than in full composites. Here, the effect of gaps and overlaps on the mechanical properties of the Fibre metal laminates (FML) is evaluated. Specimens are manufactured with a specified width of gaps/overlaps and the mechanical performance of the panels is evaluated by some selected mechanical tests. Gaps show to have a considerable effect on the mechanical performance of FML. Compression strength of samples with overlaps was rather increased. Discussions are presented on the influence on each mechanical property according to the severity of the defect (gaps/overlap) and the failure mode(s) under consideration.